(untitled) (Repertorio Científico, 2023)
Introduction: Management competencies and their developing are now, in Finland, more actual than they have been earlier. It is because Finland is currently facing a major health and social services reform; so, managers have to be able to succeed the development of a new organization, and they need to involve and support staff in the change process. In addition to managing, the development of a new organization, managers must be able to involve and support employees in change. In change managing, managers communication competencies are relevant and important for guiding and engaging employees. Objective: The aim of this study was to investigate the management competencies of managers and supervisors in the social and health care sector, in North Savo, before the reform of the health and social services. Methods: The study was conducted as a Webropol survey among managers of 13 different organizations in the North Savo region, Finland. The participant managers answered questions about their own situation and rated their competences on a Likert scale. The results were analyzed using statistical methods. Results: Almost 20% of the respondents were over 60 years old. Nearly, all respondents had studied management in addition to their degree. Preliminary results showed that 32% of the managers had not consciously chosen the management method they used. Among those managers who had consciously chosen a management method, 26% had chosen coaching management, 11% had chosen leading with knowledge and 7% had chosen positive management. 10% of respondents were using more than one management method. The results showed that the weakest areas of management competencies were quality assessment related to quality programs, business competencies, service chain design, and interdisciplinary collaboration. On the other hand, relationship building, dealing with conflict situations, professional competencies and substantive competencies of employees were the greatest strengths. Conclusions: The identified weaknesses in the study represent important areas for improvement.